Prominent Agroforestry Systems and Important Multipurpose Trees in Farming System of Mizoram - Lalramnghinglova, J. H.; Jha, L. K. (Indian Forester, 1996)
Mizoram is situated in the extreme South-eastern corner of North-East India. The affected area under slash and burn farming still bears hard on soil condition and ecology of Mizoram. However, over the years, peasants of Mizoram have been practicing various forms of agroforestry. A large number of multipurpose trees and shrurbs(48 species recorded) are left deliberately or introduced in cropping system to increase the productivity. Govt. policy of promoting new farming technique, viz; Jhum Control Project - 1987 would have gone some way to relieve the compulsion of practicing Shifting Cultivation. The most common and successful practice is intercropping of Oryza sativa (Paddy) with Tectona garndis (Teak). This system is economically and ecologically sound.